Release strategies of Telenomus podisi for control of Euschistus heros: a computational modeling approach - Weber, Igor Daniel; Garcia, Adriano Gomes; Bueno, Adeney de Freitas; Oliveira, Regiane Cristina de [UNESP]; Godoy, Wesley Augusto Conde (Wiley, 2022)
BACKGROUND: The egg-parasitoid wasp Telenomus podisi has received attention as a biological-control agent for one of the most important soybean pests in Brazil, the stink bug Euschistus heros. As yet, no studies have conclusively established strategies for the release of T. podisi. We developed a computational model using cellular automata in the C programming language to investigate release strategies for T. podisi in soybean crops, in order to optimize the use of these wasps in managing E. heros, assuming a two-dimensional grid of cells corresponding to a soybean field. RESULTS: The release strategies capable of maintaining an E. heros population below the Economic Threshold level involved releasing a total of at least 15 000 female parasitoids per hectare, in three or four releases of 5000 or more (equivalent to approximately 7142 or more male and female parasitoids per hectare, assuming a sex ratio of 0.70). A 25-m spacing between release points or strips was indicated. The model is very sensitive to the variation in the number of parasitoids per release and in the number of releases, but little sensitive to the release mode and spacing values. CONCLUSION: The theoretical results produced by the computational model are expected to guide future field studies to improve T. podisi release plans for managing E. heros in soybeans. Therefore, we recommend the release strategy of three to four releases of 5000 or more female parasitoids per hectare, at points or strips spaced 25 m apart, to be tested in field experiments for proper implementation by producers. © 2022 Society of Chemical Industry.
Keywords: biological control; cellular automata; egg parasitoids; integrated pest management